From mycelia to mastodons – A general approach for simulating biotic disturbances in forest ecosystems. (April 2021) - Honkaniemi, Juha; Rammer, Werner; Seidl, Rupert
Abstract: Forest disturbance regimes are changing around the globe. Of particular concern are biotic disturbance agents, as they respond strongly to climate warming and invade new ecosystems as alien pests and pathogens. To date, biotic disturbances are either ignored in simulations of vegetation dynamics or only a small number of common agents are considered explicitly. Here we present BITE, a general, process-based approach to simulate biotic forest disturbance agents from fungi to large mammals. BITE considers the processes of agent introduction, dispersal, colonization, population dynamics, and vegetation impact explicitly. Here we parameterize the model for six widely different biotic disturbance agents ( Heterobasidion annosum, Hymenoscyphus fraxineus, Lymanthia dispar, Anoplophora glabripennis, Capreolus capreolus, Mammut americanum ) and evaluate it using pattern-oriented modeling. BITE enables the inclusion of both established and novel biotic disturbance agents in vegetation models, and is a step towards the comprehensive simulation of forest disturbance regimes in a changing world. Highlights: The importance of biotic disturbance agents is increasing with the global change. BITE is a general approach to simulate the impacts of biotic agents on forests. Modular framework enables simulations with evolving level of knowledge on agent biology. The functionality of BITE is here illustrated with six widely different agents.